Assessment of LEED Green Building Certificate Indoor Evironmental Quality Parameters from the Perspective of Occupant Satisfaction and Cost Performance - Isik, Zeynep (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2016)
This paper presents a comparative analysis of different stakeholders' view of LEED certified building projects' Indoor Environmetal Quality (IEQ) parameters from the perspective of such key performance indicators (KPIs) as occupant satisfaction and project cost performance. Within this context, a comprehensive literature review respresenting the studies on Indoor Environmental Quality with a relationship to occupant satisfaction in terms of thermal comfort, daylighting, acoustic control and project cost premium and investment performances etc. was conducted and an Analytical Hierarchy Process (AHP) model was constructed indicating the effects of IEQ parameters on Occupant Satisfaction and Project Cost Performance. The ratings of the effects of the parameters were collected by a brainstorming workshop with the participation of different stakelholders of sustainable design such as researchers, practitioners and LEED consultants. The data were analysed conducting AHP analysis which is a multi crtieria decision method. The analysis results revelaed that thermal comfort, interior lighting, daylight, acoustic performance and environmental tobacco smoke control parameters had the highest rankings among occupant satisfaction whereas low emitting materials, daylight, thermal comfort and acoustic performance were the ones for project cost performance.
Keywords: Analytical hierarchy process (AHP); indoor environmental quality (IEQ); LEED Certification; occupant satisfaction; project cost performance; stakeholder perceptions; ENVIRONMENTAL-QUALITY; COMFORT; IMPACT; Architecture